Designing Port Passenger Terminal in the Meat Village as Ecotourism Area with Neo Vernacular Architecture Approach - Fitri Rahmawati Nasution; Moehammed Nawawiy Loebis (International Journal of Architecture and Urbanism, 2020)
This journal is essential for social, economic, and government in the Meat Village. It is about a potentially marine tourism destination, located in Meat Village, Tampahan District, Toba Samosir Regency, North Sumatra Province. As one of the tourism destinations, this village needs to be developed, especially water transportation, which is supported by Lake Toba's natural resources. But it has been replaced by land and air transportation. On the other hand, water transportation has its privilege, namely giving a sense of being united with nature and listening to the gentle sound of water, which cannot be felt if using land or air transportation. Therefore, it requires a passenger port to facilitate tourists in accessing this tourism village through water transportation. This port consists of a passenger terminal that accommodates passengers' departure and arrival. The method used in site selection is done through discussion of primary data, namely data sources that directly provide data to data collectors and secondary data, that is, data that does not directly provide data to researchers, through other people or analyzed documents and concluded. The result of the methodology used is, this passenger terminal needs the Neo Vernacular Architecture approach for the design. Because the village has aspects of the past, such as Batak Toba culture and mythology that need to be preserved and introduced to the present as long-term projections for the future. This is useful to make the building becomes part of the Meat Village community.